"Would You Like to Hear a Story?": Collaborating With Families Using Photo-Elicitation. (March 2022) - Hile, Kimberly A.; Santos, Rosa Milagros
Research related to family empowerment and capacity-building suggests that families facing multiple risk factors (e.g., presence of a disability, poverty, single parents, low levels of maternal education, etc.) may experience feelings of powerlessness when asked by professionals to make decisions on behalf of their families. The purpose of this study was to explore a particular strategy for engaging families experiencing multiple risk factors, including caring for young children with disabilities, to work collaboratively with Head Start professionals when planning and implementing family-centered interventions. Specifically, we examined how photo-elicitation may empower families to share their personal stories as a pathway to building meaningful relationships with their Head Start family service workers. A qualitative approach via thematic analysis was used. Findings begin to address the need for identifying innovative strategies for building family capacity with Head Start families, specifically those caring for young children with disabilities.